A SOCIOLOGICAL ANALYSIS OF THE FOREIGN POLICY OF GEORGIA-2016: THERE IS STILL A CHANCE FOR RUSSIA - A. A. Tokarev; A. S. Dyogtev; A. R. Margoev (Vestnik MGIMO-Universiteta)
The authors study the sociological grounds of Georgia's foreign policy based on the long-term researches conducted by American and Georgian NGOs, yet applying a critical approach to the provided data and figures. Despite the aggressive rhetoric of Georgian politicians towards Russia and apparent social consensus as regards EU and NATO integration, the article concludes that Russia has not completely "lost" Georgia. The results of the sociological surveys show that up to one third of the population of Georgia are ready to consider Russia as main partner of their country, and this figure depends to a certain extent on the Georgian authorities' policy. In addition, the potential of the Eurasian integration of Georgia is not equal to zero, and it is supported by around one fifth of the population. In the authors' view, Georgia may appreciate help with solving its domestic economic problems far more than being called "a beacon of democracy" or "a truly European state". Although according to the results of the most surveys Russia takes the first place in the list of the threats to Georgia, exceeding even the figures for the banned "Islamic State", around one third of the population of Georgia consistently consider Russian threat exaggerated. Together with those who do not regard Russia as a threat at all, these citizens of Georgia almost equal the number of people who believe that "Russia poses a threat to Georgia". Even if Russia does not change its position on the recognition of Abkhazia and South Ossetia, and the West remains the goalpost of Georgia's foreign policy, the ties between the people, cultures, and economies of the two countries will not be severed. However, negligence towards the potential of developing the bilateral relations with no efforts taken on a mutual basis may significantly weaken the ties between Russia and Georgia by undermining the chances of strengthening them.